Auto-ubiquitination of NEDD4-1 Recruits USP13 to Facilitate Autophagy through Deubiquitinating VPS34 - Xie, Weihong; Jin, Shouheng; Wu, Yaoxing; Xian, Huifang; Tian, Shuo; Liu, Di-Ao; Guo, Zhiyong; Cui, Jun (Cell reports (Cambridge), 2020)
The class III phosphoinositide 3-kinase vacuolar protein sorting 34 (VPS34) is a core protein of autophagy initiation, yet the regulatory mechanisms responsible for its stringent control remain poorly understood. Here, we report that the E3 ubiquitin ligase NEDD4-1 promotes the autophagy flux by targeting VPS34. NEDD4-1 undergoes lysine 29 (K29)-linked auto-ubiquitination at K1279 and serves as a scaffold for recruiting the ubiquitin-specific protease 13 (USP13) to form an NEDD4-1-USP13 deubiquitination complex, which subsequently stabilizes VPS34 to promote autophagy through removing the K48-linked poly-ubiquitin chains from VPS34 at K419. Knockout of either NEDD4-1 or USP13 increased K48-linked ubiquitination and degradation of VPS34, thus attenuating the formation of the autophagosome. Our results identify an essential role for NEDD4-1 in regulating autophagy, which provides molecular insights into the mechanisms by which ubiquitination regulates autophagy flux. [Display omitted] •NEDD4-1 promotes autophagy through inhibiting K48-linked ubiquitination of VPS34•NEDD4-1 recruits USP13 to deubiquitinate VPS34•Auto-ubiquitination of NEDD4-1 is required for its interaction with USP13 and VPS34 Xie et al. demonstrate that HECT ubiquitin E3 ligase NEDD4-1 undergoes lysine 29 (K29)-linked auto-ubiquitination and serves as a scaffold to recruit the ubiquitin-specific protease 13 (USP13) to form a deubiquitination complex, which subsequently stabilizes VPS34 to promote autophagy through the removal of K48-linked poly-ubiquitin chains on VPS34.